Functionalised bicyclic tetramates derived from cysteine as antibacterial agents. Issue 22 (23rd May 2019) - Panduwawala, Tharindi D.; Iqbal, Sarosh; Thompson, Amber L.; Genov, Miroslav; Pretsch, Alexander; Pretsch, Dagmar; Liu, Shuang; Ebright, Richard H.; Howells, Alison; Maxwell, Anthony; Moloney, Mark G.
Abstract : Carboxamido tetramates derived from a bicyclic skeleton provide access to compounds with antibacterial activity. Abstract : Routes to bicyclic tetramates derived from cysteine permitting ready incorporation of functionality at two different points around the periphery of a heterocyclic skeleton are reported. This has enabled the identification of systems active against Gram-positive bacteria, some of which show gyrase and RNA polymerase inhibitory activity. In particular, tetramates substituted with glycosyl side chains, chosen to impart polarity and aqueous solubility, show high antibacterial activity coupled with modest gyrase/polymerase activity in two cases. An analysis of physicochemical properties indicates that the antibacterially active tetramates generally occupy physicochemical space with MW of 300–600, clog  D 7.4 of −2.5 to 4 and rel. PSA of 11–22%. This work demonstrates that biologically active 3D libraries are readily available by manipulation of a tetramate skeleton.